Distraction Lengthening of First Metacarpal in Traumatic Thumb Amputations - Saleem, Abid; Sharma, Ramesh Kumar; Kumar, Parmod (Indian Journal of Plastic Surgery, 2019)
Introduction Based on the level of the thumb loss, phalangization, toe-to-thumb transfer, pollicization, and distraction callotasis of the first metacarpal are the various options available for reconstruction. The aims of the study were to observe the length gained in the distraction process, duration of treatment required, functional recovery in the form of pinch strength, sensations, and patient satisfaction.Patients and Methods It was a prospective study of 10 patients of thumb amputation, conducted from January 2014 to July 2015. The patients’ age, mode of injury, level of amputation, and advantages and disadvantages of distraction callotasis were evaluated.Results The most common etiology of thumb loss was domestic accidents while working with a chaff cutter. The total duration of treatment was 124 (93–165) days and the mean gain in length was 25 (20–28) mm. The pinch strength increased from a mean of 0.91 to 2.06 kg, i.e., a 44.17% improvement from preoperative pinch strength. All of our patients retained their sensations of the reconstructed thumb post distraction.Conclusions Among many options for thumb reconstruction, distraction callotasis is a simple and safer option in the selective group of patients who are not keen on toe-to-thumb transfer which provide a significant improvement. The longer duration of treatment is the disadvantage associated with the need for proper counselling beforehand.
Keywords: thumb amputation; distraction; callotasis; phalangization; pollicization